Die 99mTc-HMPAO Leukozytenszintigraphie in der Entzündungsdiagnostik am Skelettsystem - Winker, H.; Reuland, P.; Müller, J.; Weller, S.; Feine, U. (Nuklearmedizin - NuclearMedicine, 1988)
Subsequent to orthopedic surgery 23 patients were studied by leukocyte scintiscanning using 99mTc-HMPAOto detect inflammation. 12 patients had all signs of bacterial infection. In 11 patients infection of the wound area was suspected. There was one false negative and no false positive scintigraphic finding. 2 patients with an unclear postoperative course after internal fracture fixation showed intensive uptake. Several days after the scan both patients developed severe bacterial infection. From that experience we conclude that the method may be of higher sensitivity than clinical symptoms. Further investigations are necessary for an accurate assessment of the method.